Calcareous Nannofossil variability controlled by Milankovitch and sub-Milankovitch periodicity in the Monte San Nicola section (Gelasian GSSP / MIS 100–104) - Bonomo, Sergio; Zanola, Elena; Incarbona, Alessandro; Di Stefano, Agata; Distefano, Salvatore; Barbagallo, Viviana; Ferretti, Patrizia; Fornaciari, Eliana; Macrì, Patrizia; Raffi, Isabella; Sabatino, Nadia; Speranza, Fabio; et al. (Marine Micropaleontology, 2024)
The Quaternary marks the beginning of the ice ages, with the establishment of a stable Northern Hemisphere ice sheet. The Monte San Nicola section, southern Sicily (Italy) is the Global Boundary Stratotype Section and Point of the Gelasian Stage of the Lower Quaternary Subseries and is attracting new attention for providing valuable information on paleoclimate evolution. Here we present a paleoenvironmental reconstruction based on new data from calcareous nannoplankton, the phytoplankton organisms that are sensitive to sea surface changes and water column dynamics. We adopt statistical and signal analysis to support our paleoenvironmental model. The most evident paleoenvironmental signal throughout the investigated interval is the contrast between the abundance patterns of placoliths and Florisphaera profunda, the former pointing to surface productivity (water column mixing, shallow nutricline), the latter to the establishment of a deep nutricline. The observed nutricline depth shift occurred with a regular precessional pace, following Northern Hemisphere summer insolation and, likely, North African monsoon activity. A significant periodicity of 8 kyr, in tune with late Quaternary Heinrich events, is also observed in nannoplankton taxa, supporting previous findings on the existence of suborbital climatic variability even at the Pliocene-Pleistocene transition.